1998
DOI: 10.1001/jama.279.18.1445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raloxifene on Serum Lipids and Coagulation Factors in Healthy Postmenopausal Women

Abstract: Context.-Raloxifene is a selective estrogen receptor modulator that has estrogen-agonistic effects on bone and estrogen-antagonistic effects on breast and uterus. Objective.-To identify the effects of raloxifene on markers of cardiovascular risk in postmenopausal women, and to compare them with those induced by hormone replacement therapy (HRT). Design.-Double-blind, randomized, parallel trial. Setting.-Eight sites in the United States. Participants.-390 healthy postmenopausal women recruited by advertisement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
205
3
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(232 citation statements)
references
References 33 publications
19
205
3
5
Order By: Relevance
“…HRT resulted in statistically significant decreases in homocysteine and fibrinogen levels among participants, a finding that is consistent with most published reports related to oral HRT use (19)(20)(21). Of note, transdermal HRT does not appear to significantly affect fibrinogen levels (19,22), whereas raloxifene seems to lower fibrinogen levels (20,23). Finally, a majority of reports regarding the effect of HRT on homocysteine concentrations indicate that both oral HRT and raloxifene decrease homocysteine levels (24)(25).…”
Section: Discussionsupporting
confidence: 84%
“…HRT resulted in statistically significant decreases in homocysteine and fibrinogen levels among participants, a finding that is consistent with most published reports related to oral HRT use (19)(20)(21). Of note, transdermal HRT does not appear to significantly affect fibrinogen levels (19,22), whereas raloxifene seems to lower fibrinogen levels (20,23). Finally, a majority of reports regarding the effect of HRT on homocysteine concentrations indicate that both oral HRT and raloxifene decrease homocysteine levels (24)(25).…”
Section: Discussionsupporting
confidence: 84%
“…Among these 59 surrogate endpoint trials that had a subsequent clinical endpoint trial, in 24 cases the clinical endpoint trial results validated the positive surrogate trials, while in 20 the subsequent clinical endpoint trial was negative (Table 3). 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 A negative surrogate endpoint trial was less likely to be followed by a positive outcome trial and we identified only 3 such examples ( P =0.02, Figure 2). …”
Section: Resultsmentioning
confidence: 99%
“…Raloxifene also causes decreases in circulating low density lipoprotein cholesterol [134] and for this reason was evaluated as a preventive for coronary heart disease in the study named raloxifene use for the heart (RUTH) ( * see footnote). Although raloxifene prevents an increase in breast cancer incidence in the RUTH trial, there is no benefit in protecting against coronary heart disease and myocardial infarction [135].…”
Section: Selective Estrogen Receptor Modulation and Chemopreventionmentioning
confidence: 99%
“…The results from the study of tamoxifen and raloxifene (STAR) ( * see footnote) in high risk postmenopausal women show that tamoxifen and raloxifene are equivalent in reducing the incidence of breast cancer but there is a decrease in the incidence of endometrial cancer, pulmonary emboli, deep vein thrombosis and endometrial hyperplasia noted with raloxifene. Raloxifene and tamoxifen, as would be expected for two SERMs, both have equivalent activity in preventing fractures [133].Raloxifene also causes decreases in circulating low density lipoprotein cholesterol [134] and for this reason was evaluated as a preventive for coronary heart disease in the study named raloxifene use for the heart (RUTH) ( * see footnote). Although raloxifene prevents an increase in breast cancer incidence in the RUTH trial, there is no benefit in protecting against coronary heart disease and myocardial infarction [135].…”
mentioning
confidence: 99%